2020
DOI: 10.22581/muet1982.2001.13
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Vegetative Cover and Surface Water Bodies in the Indus Delta, Pakistan

Abstract: Under the current scenario of diminishing Indus River flows and changing the climate, the Indus Delta, the world’s 5th largest delta which has undergone rapid changes in water bodies and vegetative cover since last few decades, is under serious risk of losing its ecological functions. Assessing the temporal variation in vegetative cover and water bodies of the Indus Delta is essential for the future planning and ecosystem management in this region. The present study quantified the temporal patterns of the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This finding aligns with the observations made by Shahab et al [24], who reported that the highest TDS values in Pakistan are typically found in the lower part of Sindh, which corroborates the results of this study. Siyal [16] has also reported that 64% of water bodies of the Indus Delta do not satisfy WHO standards for drinking water in terms of TDS, which is in accordance with the results of this study. Data depicted that at about 57 km from the ocean, the river water maps with the limit of WHO in terms of TDS and EC.…”
Section: Total Dissolved Solids (Tds)supporting
confidence: 90%
See 3 more Smart Citations
“…This finding aligns with the observations made by Shahab et al [24], who reported that the highest TDS values in Pakistan are typically found in the lower part of Sindh, which corroborates the results of this study. Siyal [16] has also reported that 64% of water bodies of the Indus Delta do not satisfy WHO standards for drinking water in terms of TDS, which is in accordance with the results of this study. Data depicted that at about 57 km from the ocean, the river water maps with the limit of WHO in terms of TDS and EC.…”
Section: Total Dissolved Solids (Tds)supporting
confidence: 90%
“…78% of the natural surface water bodies have been reported to be saline in the delta which is because of the seawater inundation. Siyal [16] reports that 66% of the surface water samples from the delta do not meet the standards of drinking water. Figure 3.…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 99%
See 2 more Smart Citations